The Efficacy of a Video Self-Modeling Intervention on Peer Social Initiation Skills of Children with Autism Spectrum Disorders (ASD) - Kabashi, Lema; Louise A. Kaczmarek (European Journal of Social Science Education and Research, 2019)
Social initiation skills are considered among the most challenging skills to acquire by children with Autism Spectrum Disorder (ASD). Generalization of social initiations is another related challenging area. Research indicates that when provided with appropriate interventions, children with ASD may enhance social initiation skills and generalize them across settings, people, and materials. This study implemented a multiple probe single subject design across three children with ASD to examine whether a video self-modeling intervention is effective in establishing a mand repertoire and other types of peer social initiations. Generalization and maintenance effects were measured in addition to the social validity of the video self-modeling intervention. While video self-modeling led to substantial improvements in almost all of the target behaviors for one participant, additional strategies were implemented for two other participants. Discussion of findings, study limitations, and future recommendations are addressed as well.